PENGARUH AROMATERAPI DENGAN MINYAK ESENSIAL TERHADAP GEJALA DEPRESI: TINJAUAN SISTEMATIS BERBASIS BUKTI - Abdullah, Dessy; Riki Nova; Wisda Widiastuti; Gangga Mahatma; Aryaldy Zulkarnaini (Nusantara Hasana Journal, 2025)
Depression is a serious mental health issue worldwide, a condition that can significantly affect a person's quality of life. Aromatherapy has emerged as a complementary therapy with the potential to alleviate symptoms of depression, offering a lower risk of side effects compared to conventional pharmacological treatments. This narrative review aims to evaluate the effectiveness of aromatherapy in reducing symptoms of depression, with a focus on the mechanisms of action of essential oils used in this therapy. A literature search was conducted using PubMed, Web of Science, and Google Scholar databases from the year 2000 to 2023. Included articles consisted of randomized controlled trials (RCTs), systematic reviews, and meta-analyses. Essential oils such as lavender, bergamot, lemon, rose, and patchouli have been shown to be effective in reducing depressive symptoms. Their effectiveness is associated with increased levels of serotonin and dopamine, as well as suppression of hypothalamic–pituitary–adrenal (HPA) axis activity. Methods of administration, such as inhalation, massage, and diffuser use, produce varying outcomes depending on the characteristics of the studied population. Conclusion: Aromatherapy has potential as an effective complementary therapy for depression. Further research is needed to strengthen the evidence of its effectiveness across diverse populations and intervention durations.